DETEKSI RADIASI GELOMBANG ELEKTROMAGNETIK DARI PERALATAN MEDIS DAN ELEKTRONIK DI RUMAH SAKIT - Nur Hudha Wijaya; Wisnu Kartika; Aulia Resti Dewi Utari (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2019)
Hypersensitivity (electrical sensitivity) is a health problem due to the influence of electromagnetic wave radiation in the form of physiological disorders characterized by neurological symptoms (disorders of the brain and nervous system) and sensitivity (sensitivity) to electromagnetic waves. In general, workplaces that use electrical energy cause electromagnetic radiation. Subjective complaints caused by electromagnetic wave radiation and other factors such as electronic equipment, medical equipment, work climate, lighting, noise etc. The purpose of this study was to analyze electromagnetic wave radiation from medical equipment related to subjective complaints of patients in hospitals. Method: The research used is explanatory research, the method used in this study is a cross sectional survey approach and statistical tests used in the survey being analyzed. The population consists of 5 patient rooms in the hospital, which have medical equipment. The results of this study indicate there is a relationship between medical equipment and other electronics to electromagnetic wave radiation experienced by patients. Another factor is the time of exposure to medical and electronic devices.